Evolving rice and wheat markets - Ahmed, Raisuddin (International Food Policy Research Institute, 2000)
Bangladesh's Green Revolution in foodgrain production has triggered a marketing revolution of far greater proportions. While production has doubled since the 1960s, marketings (the proportion of harvest a farmer sells) have increased by a factor of six. Yet rice and wheat markets remain different in scale, structure, and performance. Historically, the performance and conduct of private marketing agents have been central to the case for direct public control of foodgrain marketing. During the great famines of 1943 and 1974, widespread concern about market malfunction and trader misconduct motivated the introduction of broad public marketing controls as well as large-scale direct public marketing of foodgrains (see Chapters 6, 7, and 11). Consequently, any major shifts in market structure or behavior will alter the fundamental premises on which large-scale public intervention was founded. To set the stage for later discussion of evolving public policy (in Chapters 6, 7, 8, 10, and 11), this chapter traces the broad changes occurring in the structure, conduct, and performance of Bangladesh's rice and wheat markets.